THE SHAPE AND SIZE OF SELLA TURCICA IN SKELETAL CLASS I, II, AND III MALOCCLUSIONS - Gulalai Jan,; Shahab Adil ,; Kainat Zeb ,; Omaima Alam,; Ghazala Wazir,; Ullah, Wahid (Journal of Ayub Medical College Abbottabad, 2024)
Background: The Sella point, located near the center of the Sella Turcica and providing cover for the pituitary gland in the skull, is one of the most frequently used cranial cephalometric landmarks for radiograph tracing. The research aimed to quantify the dimensions and delineate the anatomy of the sella turcica across various skeletal shapes. Methods: 180 subjects, aged 9 to 27 years, including 91 men and 89 females, had lateral cephalometric radiographs. These subjects were divided into three skeleton classes: Class I, II, and III, with 60 subjects in each group. Measurements of the length, depth, and anteroposterior diameter were made, and the shape was examined using linear dimensions. The difference in linear dimensions was determined using a student t-test, and the link between sella turcica size and skeletal types was examined using a one-way analysis of variance (ANOVA). When comparing the age groups, the older group's linear dimensions were bigger than the younger group's (p < 0.01). Male and female length differences were found to be significantly different (p <0.05). The length and diameter of the skeletons differed significantly from the sella size when compared. Sixty-one percent of the individuals had normal-appearing sella turcica. Further research addressing the sella turcica in the South Indian population can use the current study's linear dimensions and form as reference standards.